Boundary estimating of urban road network for traffic impact analysis when reconstructing intersections: methodology and evaluation. (2018) - Ma, Yingying; Zeng, Ying
Intersections are major points of conflict for road users and the key parts of urban road network. It is necessary to reconstruct some intersections to improve capacity and safety. A methodology to estimate the boundary of a road network for traffic impact analysis of intersection improvements is discussed in this paper. Firstly, models are presented for two types of degrees of correlation. The degree of saturation and free-flow travel time are considered in the model for the degree of correlation between two adjacent intersections, and the degree of correlation between any two intersections in the network is analysed using a Laplacian matrix algorithm. Secondly, a new method for estimating a road network boundary is proposed. Thirdly, two measures are adopted to evaluate the boundary of road networks: the minimum average cut degree of correlation and the minimum traffic influence on intersections outside the boundary. Finally, the method is demonstrated using a city road network. The results of the case study confirm the validity of the proposed approach.